2020
DOI: 10.1002/da.23092
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation‐induced increase in circulating omega‐3 serum levels is not associated with a reduction in depressive symptoms: Results from the MooDFOOD depression prevention trial

Abstract: Background There is ambiguity on how omega‐3 (n‐3) polyunsaturated fatty acids (PUFAs) are associated with depression, and what the temporality of the association might be. The present study aimed to examine whether (intervention‐induced changes in) n‐3 PUFA levels were associated with (changes in) depressive symptoms. Methods Baseline, 6‐ and 12‐month follow‐up data on 682 overweight and subclinically depressed persons from four European countries that participated in the MooDFOOD depression prevention random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…An increasing number of dietary or nutrient-based interventions are investigated to be effective in preventing and managing psychiatric disorders ( 58 ). However, our research found that supplementation of n-3 PUFAs does not effectively improve depressive symptoms, which is consistent with previously reported studies ( 59 , 60 ). One possible explanation is that the antidepressant effect of venlafaxine was too strong.…”
Section: Discussionsupporting
confidence: 93%
“…An increasing number of dietary or nutrient-based interventions are investigated to be effective in preventing and managing psychiatric disorders ( 58 ). However, our research found that supplementation of n-3 PUFAs does not effectively improve depressive symptoms, which is consistent with previously reported studies ( 59 , 60 ). One possible explanation is that the antidepressant effect of venlafaxine was too strong.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, some clinical trials failed to demonstrate the efficacy of LC-PUFA, either alone or associated with pharmacological or behavioral interventions, in patients with depression (90)(91)(92)(93).…”
Section: Therapeutic Opportunities For Food Supplements In Depression: Evidence Limitations and Suggestions For The Futurementioning
confidence: 99%
“…12 In contrast, supplementation with multi-nutrients in the randomized controlled trial MooDFOOD did not affect the persistence of major depression in subclinical and overweight depressed subjects. 13 A study performed on the data of adult subjects from the 9-year follow-up of the Depression and Anxiety Netherlands Study showed a dose-response association between the severity of chronic depression or anxiety disorders and a poorer diet quality in all study participants. 14 Overall, the recent findings from clinical trials seem to support the use of a complex of care measures including first line pharmacological and psychological treatments, as well as lifestyle interventions (e.g.…”
Section: Introductionmentioning
confidence: 98%